Incandescent metasurfaces: A tutorial - Jean-Jacques Greffet; Benjamin Vest; Patrick Bouchon; Bo Zhao (APL Photonics)
Incandescence has long been the most popular source of light, despite a number of limitations in terms of efficiency, polarization, and coherence. In the last twenty years, it has been shown that most of these limitations can be overcome by taking advantage of the advances in nanophotonics. In this paper, we provide a tutorial presentation of the field with emphasis on the fundamental principles used to control the properties of thermal radiation in the far field. We introduce several figures of merit and list some directions for future work.